PROTOCOL: Value chain interventions for improving women's economic empowerment: A mixed‐method systematic review - Malhotra, Suchi Kapoor; Saran, Ashrita; Singh, Sabina; Mantri, Swati; Gupta, Neha; Bhandari, Ratika; White, Howard; Puskur, Ranjitha; Young, Sarah; Waddington, Hugh; Masset, Edoardo (Wiley, 2023)
This is the protocol for a Campbell systematic review. The objectives are as follows: The primary objective of this review is to understand as well as evaluate what approaches, strategies or interventions focused on women's engagement in agricultural value chains and markets that have led to women's economic empowerment in low‐and‐middle‐income countries. The secondary objective of this review is to examine in which contexts are these approaches effective (or ineffective)? What are the contextual barriers and facilitators, determining the participation of women in, and benefits from, engagement in the value chain in low‐and middle‐income countries programme effectiveness. Finally, this review aims to refine the theory of change that describes how value chain interventions lead to women's economic empowerment using evidence drawn from both rigorous quantitative impact evaluation studies and qualitative studies.